COMMUNITY REVITALIZATION STRATEGY IN AKSARA INCUNG - Nurcahya, Yan; Oksa Putra, M Zikril; Syah, Muhammad Kautsar Thariq; Supriadi, Dedi; Sugiarto, Deri; Hambaliana, Dandie (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2024)
The Aksara Incung is an old Kerinci script that is threatened with extinction because it is no longer known by the Kerinci community. The Kerinci script is a cultural heritage of Kerinci and a source of pride for the Kerinci community. However, with the emergence of Islamic civilization and the Dutch colonial period, many Kerinci people began to be introduced to new cultures, resulting in fewer and fewer people studying, teaching and implementing the existence of the incung script in everyday life. The objectives of the study were (1) to explain the development of the Kerinci Incung script batik motif, (2) to express ideas derived from the Kerinci Incung script in the creation of craft works of art in the form of stamped batik motifs and (3) to understand and explore the meaning contained in the Kerinci Incung script as a cultural product of the community in the past. The research method used a qualitative approach. with observation, documentation and interviews with batik craftsmen and activists. Data collection was carried out using the purposive sampling method and the research location was Kerinci Regency and Sungai Penuh City. The method of creating Incung script motifs includes three stages, namely the exploration stage, the design/motif making process stage and the realization process. The Incung script revitalization strategy in the community is one way to reintroduce and preserve the Incung script. through painting media starting from motifs on Kerinci batik, motifs on musical instruments, establishing an Incung script school, bringing up Incung on every place name, street name, office name in the Kerinci area, and teaching school children by bringing up additional subjects. So that all of this can facilitate the effort to introduce the Incung script to the community.